Early Amplified Respiratory Bioactive Lipid Response Is Associated With Worse Outcomes in Pediatric Influenza-Related Respiratory Failure. (9th April 2020) - Anania, Veronica G; Randolph, Adrienne G; Yang, Xiaoying; Nguyen, Allen; Newhams, Margaret M; Mathews, W Rodney; Rosenberger, Carrie M; McBride, Jacqueline M
Abstract: Background: Biomarkers are needed for early identification of patients at risk of severe complications from influenza infection, including prolonged respiratory failure and death. Eicosanoids are bioactive lipid mediators with pro- and anti-inflammatory properties produced in response to infection. This study assessed the relationships between the host bioactive lipid response, influenza viral load, and clinical outcomes. Methods: Influenza-positive, intubated children ≤18 years old were enrolled across 26 US pediatric intensive care units (PICUs). Mass spectrometry was used to measure >100 lipid metabolites in endotracheal and nasopharyngeal samples. Influenza viral load was measured by quantitative polymerase chain reaction. Results: Age and bacterial co-infection were associated with multiple bioactive lipids ( P  < .05). Influenza viral load was lower in patients with bacterial co-infection compared with those without, and pro-inflammatory bioactive lipids positively correlated with viral load in bacterially co-infected children ( P  < .05). Lipids associated with disease resolution correlated with viral load in patients without bacterial co-infection ( P  < .01). After adjusting for age and bacterial co-infection status, elevated pro- and anti-inflammatory lipids measured early in the intensive care unit course were associated with higher mortality, whereas influenza viral load and endotracheal cytokine levels were not associated with clinical outcomes. Prostaglandin E2, arachidonic acid, docosahexaenoic acid, and 12-hydroxyeicosatetraenoic acid measured within 72 hours of PICU admission predicted death or prolonged (≥28 days) mechanical ventilator support (area under the curve, 0.72–0.79; P  < .02) not explained by admission illness severity. Conclusions: Children with influenza-related complications have early bioactive lipid responses that may reflect lung disease severity. Respiratory bioactive lipids are candidate prognostic biomarkers to identify children with the most severe clinical outcomes.